Duplex Telomere-Binding Proteins in Fungi With Canonical Telomere Repeats: New Lessons in the Rapid Evolution of Telomere Proteins - Lue, Neal F. (Frontiers in Genetics, 2021)
The telomere protein assemblies in different fungal lineages manifest quite profound structural and functional divergence, implying a high degree of flexibility and adaptability. Previous comparative analyses of fungal telomeres have focused on the role of telomere sequence alterations in promoting the evolution of corresponding proteins, particularly in budding and fission yeast. However, emerging evidence suggests that even in fungi with the canonical 6-bp telomere repeat unit, there are significant remodeling of the telomere assembly. Indeed, a new protein family can be recruited to serve dedicated telomere functions, and then experience subsequent loss in sub-branches of the clade. An especially interesting example is the Tay1 family of proteins, which emerged in fungi prior to the divergence of basidiomycetes from ascomycetes. This relatively recent protein family appears to have acquired its telomere DNA-binding activity through the modification of another Myb-containing protein. Members of the Tay1 family evidently underwent rather dramatic functional diversification, serving e.g., as transcription factors in fission yeast while acting to promote telomere maintenance in basidiomycetes and some hemi-ascomycetes. Remarkably, despite its distinct structural organization and evolutionary origin, a basidiomycete Tay1 appears to promote telomere replication using the same mechanism as mammalian TRF1, i.e., by recruiting and regulating Blm helicase activity. This apparent example of convergent evolution at the molecular level highlight the ability of telomere proteins to acquire new interaction targets. The remarkable evolutionary history of Tay1 illustrates the power of protein modularity and the facile acquisition of nucleic acid/protein-binding activity to promote telomere flexibility.